Zakwestionowana dychotomia? W poszukiwaniu nowego paradygmatu poznawczego dla studiów nad współczesnym społeczeństwem obywatelskim - Misztal, Wojciech; Kościański, Artur (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2023)
The following discussion is an attempt to respond to the growing need for a renewed reflection on civil society, which has become increasingly evident in recent years. By interpreting the intentions of researchers and theoreticians working on the topic of civil society, we can find new sources of inspiration both for the civic idea and for the further development of the study of the ways in which people come together in civic alliances in the modern world. To this end, we propose that researchers (re)focus on the category of patterns of civic engagement as a basis for both associative relations and the recognition of certain products of these relations as “relational common goods.” In our opinion, patterns of civic engagement should be seen as a process of acquiring certain traits (such as skills, personality dispositions, attitudes, etc.) rather than as a closed set of qualities of a “good citizen.”